The comparison of psychological hardiness and resilience against educational stressors among veterans and non-veterans progeny students - Bahadorikhosroshahi, Jafar; Habibi-Kaleybar, Ramin (Researcher Bulletin of Medical Sciences, 2018)
Background and Aim: Martyrs and veterans progeny students have unique status due to their special life condition comparing with non-veteran students. The aim of this study is to compare the psychological hardiness and resilience against educational stressors in veterans and non-veteran students. Materials and Methods: Causal-comparative research method was utilized for this study. Sample population included all veterans and non-veterans high school students of Ilkhechi (Tabriz) in the academic year of 2016 and 2017. Sample of 80 students (40 veterans and 40 normal students) were randomly selected using Cochran formula. Data collection tools included Kobasa Hardiness Scale and Connor-Davidson Resilience Scale. For data analysis, MANOVA were performed, using SPSS version 19. The significance level was considered to be 0.05. Results: Results showed that there are significant differences in the psychological hardiness and resilience variables between veteran and non-veteran students (P<0.001). Based on the results, veteran students are less than average in psychological hardiness and resilience variables. Conclusion: Our results, consistent with previous findings,indicate that students with high levels of psychological hardiness and resilience are able to maintain their psychological health in stressful and tough situations and are more prone psychological adaptation.